The First Genome Assembly Of The Dogwhelk Nucella lapillus, a Bioindicator Species For The Marine Environment - Juned Kadiwala; Andrew Hesketh; Heleen De Weerd; Helen Ritch; Rameen Shakur (Scientific Data)
Abstract The dogwhelk (Nucella lapillus) is a predatory marine gastropod widely distributed across temperate intertidal zones. Renowned for its ecological role in controlling prey populations, N. lapillus is also an important bioindicator species for marine pollution through imposex. The molecular genetic basis of imposex, characterised by the abnormal development of male sex organs in females and reductions in fertility and lifespan, however remains poorly understood due to the absence of a reference genome sequence. Here we provide the first genome assembly comprising 2.41 Gb of sequence, predicted to encode 47,238 proteins. This inaugural assembly lays the foundations for implementing genomic approaches to better quantify and characterise imposex, in addition to elucidating adaptations to life within changeable intertidal ecosystems. To counter challenges of DNA fragmentation and contamination often associated with the sequencing of marine organisms, we found that a hybrid approach that integrates complementary long-read data from PacBio HiFi and Oxford Nanopore Technology (ONT) platforms helped maximise the final assembly. This innovative combination may be a useful approach for similar marine species.